Branding Malaysia as food tourism destination among tourist - Maryanne Tong Ying Ying; Mohamad Syafie Sugianto; Siti Nur Azeera Sha'ri; Siti Nur Halimah Md Yunos (2021)
This study is about Branding Malaysian as a food tourism destination among tourists. As a multi-racial country, Malaysia's colorful culture and history is reflected in its food. Historically, Malaysian cuisine and its special tastes and traditions come from global immigrants from various countries, such as Arabia, China, India, Thailand, Indonesia, and Portugal. The various types of food in Malaysia have created a picture of society, which represents the multi-racial society in the region, exchanging cultures and food diversity. Therefore, this study is to identify the factors that make Malaysia as food tourism destination. This study employed quantitative approach by using questionnaire as the research instrument. About 207 Malaysians participated in this study. The results of this study show that there is a significant relationship between authenticity of food, diversity of food, halal food and affordable price of food with branding Malaysia as a food tourism destination among tourists. The highest score of 0.740 is halal food which make Malaysia as a food tourism destination